2013
DOI: 10.1111/imm.12051
|View full text |Cite
|
Sign up to set email alerts
|

SNX3 recruits to phagosomes and negatively regulates phagocytosis in dendritic cells

Abstract: SummaryPhagocytes such as dendritic cells (DC) and macrophages employ phagocytosis to take up pathogenic bacteria into phagosomes, digest the bacteria and present the bacteria-derived peptide antigens to the adaptive immunity. Hence, efficient antigen presentation depends greatly on a well-regulated phagocytosis process. Lipids, particularly phosphoinositides, are critical components of the phagosomes. Phosphatidylinositol-3,4,5-triphosphate [PI(3,4,5)P 3 ] is formed at the phagocytic cup, and as the phagosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…Phagocytosis by macrophages for ingestion and degradation of microbes is not only the first line of defense in the innate immune response to infection but is also important for antigen processing and presentation, which helps to drive the adaptive immune response. Although some SNX family proteins, such as SNX3 and SNX5 [ 29 , 30 ], have been shown to affect phagocytosis, our results suggested that SNX10 deficiency did not affect the phagocytosis of macrophages following bacterial infection. However, loss of SNX10 decreased the efficiency of killing L. monocytogenes .…”
Section: Discussioncontrasting
confidence: 59%
“…Phagocytosis by macrophages for ingestion and degradation of microbes is not only the first line of defense in the innate immune response to infection but is also important for antigen processing and presentation, which helps to drive the adaptive immune response. Although some SNX family proteins, such as SNX3 and SNX5 [ 29 , 30 ], have been shown to affect phagocytosis, our results suggested that SNX10 deficiency did not affect the phagocytosis of macrophages following bacterial infection. However, loss of SNX10 decreased the efficiency of killing L. monocytogenes .…”
Section: Discussioncontrasting
confidence: 59%
“…Importantly, SNX3 has been described to localize to phagosomes in human dendritic cells ( Chua and Wong, 2013 ) and to SCVs in HeLa cells ( Braun et al, 2010 ), the latter also involving PI(3)P, Rab5, and the generation of membrane tubules. However, there are important differences between these earlier models and the pathway that we describe here.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that gene silencing of EhSNX2, but not EhSNX1, increased the trogocytosis efficiency was counter-intuitive and suggestive of EhSNX2 being a negative regulator of trogocytosis. It has been shown that in dendritic cells, SNX3 overexpression causes defect in early endosome maturation by competing PI3P on early endosomes and reducing EEA1 recruitment (Chua & Wong, 2013). This observed phenotype may mirror the apparent upregulation of trogocytosis by…”
Section: Pip Specificity Of Ehsnx1/2 and Human Snxsmentioning
confidence: 93%
“…It has been shown that in dendritic cells, SNX3 overexpression causes defect in early endosome maturation by competing PI3P on early endosomes and reducing EEA1 recruitment (Chua & Wong, 2013). It has been shown that in dendritic cells, SNX3 overexpression causes defect in early endosome maturation by competing PI3P on early endosomes and reducing EEA1 recruitment (Chua & Wong, 2013).…”
Section: Pip Specificity Of Ehsnx1/2 and Human Snxsmentioning
confidence: 99%